191k views
4 votes
Question 3(Multiple Choice Worth 2 points)

(01.06 MC)
Simplify √√-72-
--6√√2
6√-2
6√√2i
061√2

Question 3(Multiple Choice Worth 2 points) (01.06 MC) Simplify √√-72- --6√√2 6√-2 6√√2i-example-1
User Dwightjl
by
4.9k points

1 Answer

4 votes

Answer:


6i√(2)

Explanation:

Given expression:


√(-72)

Rewrite -72 as the product of 6 · -1 · 2:


\implies √(36 \cdot -1 \cdot 2)

Apply the radical rule
√(ab)=√(a)√(b):


\implies √(36) √(-1) √(2)

Carry out the square root of 36:


\implies 6√(-1)√(2)

Apply the imaginary number rule
√(-1)=i :


\implies 6i√(2)

User Bas Slagter
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.